The Influence of Pocket Money on the Desire to Learn Mathematics Among Elementary School Students - Siswanto, Deny Hadi; Hanama, Akhmad (The Indonesian Institute of Science and Technology Research, 2024)
This study aims to investigate the relationship between the provision of pocket money and the level of desire for mathematics learning among 6th-grade students at SD. Muhammadiyah Pulokadang, Bantul, Indonesia (a private elementary school). This study employs a symmetric correlational methodology with 30 students participating as the sample. Information was collected through the questionnaires and the examination of relevant documentation. Data analysis was performed using descriptive statistical techniques and inferential statistical methods. The results of the descriptive analysis indicate that the average score for the pocket money questionnaire was 59.23, indicating a sufficient category, while the average score for the desire to learn mathematics questionnaire was 66.40, indicating a good category. The regression coefficient results, with a significance level set at 5%, yielded a significance value of 0.021, which is less than 0.05. Based on these findings, there is a significant and positive relationship between the provision of pocket money and the level of desire to learn mathematics among students. Additionally, this also suggests that the provision of pocket money can have a positive influence on the level of desire to learn mathematics among 6th-grade students.